Memory regimes, struggles over resources and ethnogenesis in the Brazilian Amazon - Edviges M. Ioris (Vibrant: Virtual Brazilian Anthropology, 2018)
The paper focuses on the ethnogenesis processes that emerged in the late 1990s in the Brazilian Amazon region, more specifically among indigenous peoples in the lower Tapajós region, in southwestern Pará. Highlighting the case of the Munduruku, alongside the Borary and Arapium, the paper approaches these ethnogeneses as constituting a new memory regime that provides the indigenous peoples with a counter- narrative to the ways that historiography and the jurisdictions of the dominant power have not only omitted, over time, but that also negated the permanence of ethnic and cultural alterities in the region. Confronting historiographical narratives that, since the mid-nineteenth century, have confirmed their disappearance from the lower Tapajós region, the indigenous peoples arrive at the turn of the twenty-first century presenting a counter-narrative to the erasure of their existence, re-establishing their presence in history of the lower Tapajós, and asserting their demands in negotiations of power. The paper also examines the motivations (material and ideological) precipitating the emergence of these ethnogenesis processes, which have taken shape in a field of disputes strongly defined by the interests of the timber industry.